Allergy approach to a dog population from a veterinary dermatology consultation at the tropical inland city of Londrina, Paraná, Brazil - Cecci, Gabriela (2019)
Background: Prevalence of allergy in dogs is also increasing associated with better living conditions and medical care. Indoor life is more often related to mite and mold sensitization and allergy, while an outdoor environment would favor a pollinic response with seasonal worsening. On the other hand, food allergy tends to present as a perennial condition. The particular frame of a tropical climate may in turn introduce environmental factors associated either with the concentration of available airborne allergens or skin barrier conditions. This study aimed to characterize the allergy frame of a dog population attending the State University of Londrina and Veterinary Clinics Life Space dermatology outpatient consultation, situated in the tropical inland region of Paraná, Brazil. Methods: A 111 allergic patient population (60 males and 51 females) was selected by clinical evaluation and submitted to food allergy restriction measures from 2015 to 2018. Thirty five patients (33.3%) belonged to predisposed breeds, 74.8% were indoor and 25.2% outdoor. Results: First signs started between 1-3 years of age in 55% of the patients and after the 3 years in 45%. Several comorbidities were found in 47.5% of the 1-3 years group and in 60% of the above group. Atopic dermatitis (AD) was diagnosed in 90.9% and food allergy (FA) in 23.7%, with 12.6% of simultaneous AD+FA. Malassezia overgrowth (MO) was diagnosed in 49.6% of the patients, mostly in the AD group. Flea allergy dermatitis was simultaneously diagnosed in 14.4% of the patients and otitis and conjunctivitis in 36% and 18.9%, respectively. Skin barrier disruption with seborrhea was diagnosed in 59% of the patients. The fourth version of the Canine Atopic Dermatitis Extent and Severity Index (CADESI-4) showed 13.5%, 33.3% and 53.2% of Light, Moderate and Severe scores, respectively, and pretty similar in the group of predisposed-breeds. Positive correlation was found between CADESI-4 scores and FA (p=0.03), seborrhea (p<0.00001), MO (p=0.00003) and otitis (p=0.01). Malassezia overgrowth correlated positively with indoor living (p=0.02) and otitis (p<0.00001) despite 29% of MO without otitis. Simultaneous flea allergy correlated negatively with MO (p=0.0079), otitis (p=0.001) and conjunctivitis (p<0.00001). Conclusion: A clear clinical worsening trend was found associated with seborrhea, FA, indoor living and otitis and MO in this tropical population. Malassezia overgrowth is probably more severe in this wet tropical environment.